Antigen-specific single B cell sorting and expression-cloning from immunoglobulin humanized rats: a rapid and versatile method for the generation of high affinity and discriminative human monoclonal antibodies. Issue 1 (December 2017) - Ouisse, Laure-Hélène; Gautreau-Rolland, Laetitia; Devilder, Marie-Claire; Osborn, Michael; Moyon, Melinda; Visentin, Jonathan; Halary, Frank; Bruggemann, Marianne; Buelow, Roland; Anegon, Ignacio; Saulquin, Xavier
Abstract Background There is an ever-increasing need of monoclonal antibodies (mAbs) for biomedical applications and fully human binders are particularly desirable due to their reduced immunogenicity in patients. We have applied a strategy for the isolation of antigen-specific B cells using tetramerized proteins and single-cell sorting followed by reconstruction of human mAbs by RT-PCR and expression cloning. Results This strategy, using human peripheral blood B cells, enabled the production of low affinity human mAbs against major histocompatibility complex molecules loaded with peptides (pMHC). We then implemented this technology using human immunoglobulin transgenic rats, which after immunization with an antigen of interest express high affinity-matured antibodies with human idiotypes. Using rapid immunization, followed by tetramer-based B-cell sorting and expression cloning, we generated several fully humanized mAbs with strong affinities, which could discriminate between highly homologous proteins (eg. different pMHC complexes). Conclusions Therefore, we describe a versatile and more effective approach as compared to hybridoma generation or phage or yeast display technologies for the generation of highly specific and discriminative fully human mAbs that could be useful both for basic research and immunotherapeutic purposes.